D-penicillamine induced degenerative dermopathy - Sujay Khandpur; Naresh Jain; Shweta Singla; Priti Chatterjee; Madhuri Behari (Wolters Kluwer Medknow Publications, 2015)
D-penicillamine interferes with elastin and collagen metabolism and produces several cutaneous and multi-systemic side-effects. We present two cases of Wilson's disease who on long-term penicillamine therapy developed drug-induced degenerative dermopathy manifesting as skin fragility over pressure sites and cutis laxa-like changes.